P09.09 Exploring the relationship between importation frequency and the persistence of gonorrhoea strains in an msm population: a modelling study. (13th September 2015) - Hui, B; Whiley, D; Donovan, B; Regan, D
Abstract : Introduction: Molecular typing of fluoroquinolone resistant isolates from the US suggests that the importation of new strains, rather than mutation within existing strains, is the main source of Neisseria gonorrhoeae (NG) antimicrobial resistance (AMR) emerging within a properly treated population. In Australia, ciprofloxacin resistance was first observed in the 1990s, rose sharply to more than 50% of isolates by 2008, and has stabilised at 30–40% highlighting the ability of imported strains to become established. With recent sporadic cases of ceftriaxone-resistant gonorrhoea reported in Australia and elsewhere, we sought to model the potential for imported NG strains to persist in the men who have sex with men (MSM) population in Australia. Methods: An individual-based model was developed to represent the transmission of NG in an urban MSM population in Australia. We assume a new NG strain is imported repetitively over the course of one year into a population where NG is already endemic and examined the likelihood that an imported strain will persist for a range of importation frequencies. In doing so, we assumed that all NG strains are of similar fitness. Results: The chance that an imported strain will persist for more than 20 years is predicted to be 4% if the importation frequency is once every six months, and increases to 24% if the importation frequency is once every month. If an anatomical site can only be infected by one NG strain at a time, the model predicts that there is a <3% chance that an imported strain will persist even if the importation frequency is once every month. Conclusion: Increasing the importation frequency increases the probability of an imported strain persisting in the population. If importation events are rare, then an imported strain is unlikely to persist unless it can coexist with local NG strains at the same anatomical site. Disclosure of interest statement: This work was supported by National Health and Medical Research Council Project Grant (APP1025517) and Program Grant (APP1071269). The Kirby Institute is funded by the Australian Government Department of Health and Ageing and is affiliated with the Faculty of Medicine, UNSW Australia. The views expressed in this publication do not necessarily represent the position of the Australian Government.